Building an Islamic Education System: A Critical Study of Theological Foundations and Educational Norms - Zhaskiyah Nur Sabillah; Siti Fatimah Zahra; Rifqi (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2026)
This study examines the theological and normative foundations of Islamic education as the primary basis for developing a holistic and adaptive educational system. Islamic education is viewed as a process of forming insan kamil (the complete human being), characterized by a balance between spiritual, moral, and intellectual dimensions, aimed at fostering closeness to Allah SWT and developing individual potential in both worldly and hereafter contexts. The normative foundation integrates Islamic ethical and moral values into the curriculum, aligning them with social values and the state constitution, such as Pancasila and the 1945 Constitution, in order to cultivate responsible and well-characterized citizens.   This research employs a qualitative method using a literature review and critical analysis to evaluate the implementation and relevance of theological and normative foundations in contemporary Islamic education. The findings highlight the importance of developing a holistic curriculum that integrates spiritual, intellectual, emotional, and social aspects, as well as implementing learning methods that are responsive to technological advancements and social dynamics. Islamic education needs to synergize with various stakeholders to address global challenges and to produce a generation that excels academically while also possessing moderate and tolerant character.